The question of the content of school history course in the publications of historians-methodologists in the 1920s and 1930s - Šenberga, Ilze (History / Istorija, 2019)
The article is the continuation of the publication The issue of social functions of history in the periodicals of Latvia in the 1920s and 1930s which was published in Istorija (2016, Vol. 102, No. 2). The article considers the views of teachers-historians about the principles of selection of historical material, its organization in the lower secondary school, their vision of the place of national history in school history education and its proportion with world history in the school curriculum.